Regional Gray Matter Volumes as Related to Psychomotor Slowing in Adults with Type 1 Diabetes - Nunley, Karen A. (Psychosom Med, 2017)
OBJECTIVE: Psychomotor slowing is a common cognitive complication in type 1 diabetes (T1D), but its neuroanatomical correlates and risk factors are unclear. In non-diabetic adults, smaller gray matter volume (GMV) and presence of white matter hyperintensities (WMH) are associated with psychomotor slowing. We hypothesize that smaller GMV in prefronto-parietal regions explains T1D-related psychomotor slowing. We also inspect the contribution of microvascular disease and hyperglycemia. METHODS: GMV, WMH, and glucose levels were measured concurrently with a test of psychomotor speed (Digit Symbol Substitution Test, DSST) in 95 adults with childhood-onset T1D (mean age/duration=49/41 years) and 135 similarly-aged non-T1D adults. Linear regression models tested associations between DSST and regional GMV, controlling for T1D, sex, and education; a bootstrapping method tested whether regional GMV explained between-group differences in DSST. For the T1D cohort, voxel-based and a priori regions-of-interest methods further tested associations between GMV and DSST, adjusting for WMH, hyperglycemia, and age. RESULTS: Bilateral putamen, but not other regions, significantly attenuated DSST differences between the cohorts (bootstrapped unstandardized indirect effects: −3.49, −3.26; 95% confidence limits [−5.49, −1.80], [−5.29 −1.44], left and right putamen, respectively). Among T1D, DSST was positively associated with GMV of bilateral putamen and left thalamus. Neither WMH, hyperglycemia, age, nor other factors substantially modified these relationships. CONCLUSIONS: For middle-aged adults with T1D and cerebral microvascular disease, GMV of basal ganglia may play a critical role in regulating psychomotor speed, as measured via DSST. Studies to quantify the impact of basal ganglia atrophy concurrent with WMH progression on psychomotor slowing are warranted.